2009
DOI: 10.1128/iai.01449-08
|View full text |Cite
|
Sign up to set email alerts
|

Unique Roles of DosT and DosS in DosR Regulon Induction and Mycobacterium tuberculosis Dormancy

Abstract: In Mycobacterium tuberculosis, the sensor kinases DosT and DosS activate the transcriptional regulator DosR, resulting in the induction of the DosR regulon, which is important for anaerobic survival and perhaps latent infection. The individual and collective roles of these sensors have been postulated biochemically, but their roles in vivo have remained unclear. This work demonstrates distinct and additive roles for each sensor during anaerobic dormancy. Both sensors are necessary for wild-type levels of DosR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 46 publications
10
119
2
Order By: Relevance
“…Further, it is reported that flavin nucleotides could help to reduce the heme iron of DosS. The heme iron of DosT can withhold the conversion of the Fe 2þ to Fe 3þ in the presence of oxygen [Honaker et al, 2009], suggesting that DosT could play a more important role than DosS in the early phase of hypoxic conditions especially when transferred from aerobic to hypoxic conditions. The C terminus of DosR can bind DNA, and the 54th conserved aspartate is essential for the binding.…”
Section: The Components and Distribution Of The Dosr Regulonmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, it is reported that flavin nucleotides could help to reduce the heme iron of DosS. The heme iron of DosT can withhold the conversion of the Fe 2þ to Fe 3þ in the presence of oxygen [Honaker et al, 2009], suggesting that DosT could play a more important role than DosS in the early phase of hypoxic conditions especially when transferred from aerobic to hypoxic conditions. The C terminus of DosR can bind DNA, and the 54th conserved aspartate is essential for the binding.…”
Section: The Components and Distribution Of The Dosr Regulonmentioning
confidence: 99%
“…The DosR regulon is regulated by the response regulator DosR. PhoP(Rv0757) can restore the DosR regulon to basal level during aerobic growth too [Gonzalo-Asensio et al, 2008;Honaker et al, 2009].…”
Section: The Expression and Regulation Of Dosr Regulonmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results and previous studies, we propose a model for the regulatory network of M. tb in response to hypoxia (Figure 7(a)). In this model, the early hypoxic response of M. tb is mediated by the DosR-DosS/T system, [23,39] which induces the expression of the DosR regulon including Rv0081 . DosR positively regulates its own expression, which forms a positive loop that continuously increases the expression of Rv0081 and other DosR-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…A set of 48 genes of dos regulon is up-regulated in stress conditions and presumably play important roles in survival of mycobacteria within the granuloma, under latency. The expression of these genes are controlled by a regulated gene cluster consisting of three genes (Rv3134c/3133c/3132c), among them, DosR (Rv3133c) functions as a cognate response regulator [1][2][3][4][5][6][7][8]. It has been shown that the cellular composition of granuloma is in a dynamic state with respect to oxygen tension [9].…”
Section: Introductionmentioning
confidence: 99%